First metatarsophalangeal joint replacement with total arthroplasty in the surgical treatment of the hallux rigidus - Valentini, Roberto; De Fabrizio, Giovanni; Piovan, Gianluca (Acta Biomedica Atenei Parmensis, 2014)
The hallux rigidus, especially in advanced stage, has always been a challenge as regards the surgical treatment. Over the years there have been various surgical techniques proposed with the aim of relieving pain, correcting deformity and maintain a certain degree of movement. For some years we have addressed the problem with the replacement metatarsophalangeal joint arthroplasty with Reflexion system. As far as our experience we have operated and monitored 25 patients (18 females and 7 males) of mean age 58.1 years, operated with this technique from June 2008 to June 2011. It reached an average ROM of 72° (extension and flexion 45° and 27°) with a good functional recovery in 8 patients, and this articulation was good (50° - 40°) in 12 patients and moderate in 5 with a articular range from 40°- 30°. The clinical results, according to our experience, appear to be favorable, as even patient satisfaction is complete.